Isoelectronic Tungsten Doping in Monolayer MoSe2 for Carrier Type Modulation. Issue 37 (6th July 2016) - Li, Xufan; Lin, Ming‐Wei; Basile, Leonardo; Hus, Saban M.; Puretzky, Alexander A.; Lee, Jaekwang; Kuo, Yen‐Chien; Chang, Lo‐Yueh; Wang, Kai; Idrobo, Juan C.; Li, An‐Ping; Chen, Chia‐Hao; et al.
Abstract : Carrier‐type modulation is demonstrated in 2D transition metal dichalcogenides as n‐type monolayer MoSe2 is converted to nondegenerate p‐type monolayer Mo1− x W x Se2 through isoelectronic doping. Although the alloys are mesoscopically uniform, the p‐type conduction in monolayer Mo1− x W x Se2 appears to originate from the upshift of the valenceband maximum toward the Fermi level at highly localized "W‐rich" regions in the lattice.